Characteristics and outcomes in patients with a prior myocardial infarction treated with extended dual antiplatelet therapy with ticagrelor 60 mg: findings from ALETHEIA, a multi-country observational study - Bonaca, Marc; Lesén, E; Giannitsis, Evangelos; Hedberg, J; Jernberg, T; Lambrelli, D; Duong, M; Maggioni, A P; Ariza-Solé, A; ten Berg, J; Storey, R F (European heart journal - cardiovascular pharmacotherapy, 2023)
Guidelines recommend extended dual antiplatelet therapy, including ticagrelor 60 mg twice daily, in high-risk post-myocardial infarction (MI) patients who have tolerated 12 months and are not at high bleeding risk. The real-world utilization and bleeding and ischaemic outcomes associated with long-term ticagrelor 60 mg in routine clinical practice have not been well described.Register and claims data from the USA (Optum Clinformatics, IBM MarketScan, and Medicare) and Europe (Sweden, Italy, UK, and Germany) were extracted. Patients initiating ticagrelor 60 mg ≥12 months after MI, meeting eligibility criteria for the PEGASUS-TIMI (Prevention of Cardiovascular Events in Patients with Prior Heart Attack Using Ticagrelor Compared to Placebo on a Background of Aspirin - Thrombolysis in Myocardial Infarction 45) 54 trial, were included. The cumulative incidence of the composite of MI, stroke, or all-cause mortality and that of bleeding requiring hospitalization were calculated. Meta-analyses were performed to combine estimates from each source.A total of 7035 patients treated with ticagrelor 60 mg met eligibility criteria. Median age was 67 years and 29% were females; 12% had a history of multiple MIs. The majority (95%) had been treated with ticagrelor 90 mg prior to initiating ticagrelor 60 mg. At 12 months from initiation of ticagrelor 60 mg, the cumulative incidence [95% confidence interval (CI)] of MI, stroke, or mortality was 3.33% (2.73-4.04) and was approximately three-fold the risk of bleeding (0.96%; 0.69-1.33).This study provides insights into the use of ticagrelor 60 mg in patients with prior MI in clinical practice. Observed event rates for ischaemic events and bleeding generally align with those in the pivotal trials, support the established safety profile of ticagrelor, and highlight the significant residual ischaemic risk in this population.Clinical Trials.gov Registration NCT04568083.
Online veröffentlicht: 31. August 2023
Gesehen am 08.12.2023